Development of a coastal information system for the management of Jeddah coastal waters in Saudi Arabia. (April 2016) - Mayerle, R.; Al-Subhi, A.; Fernández Jaramillo, J.; Salama, A.; Bruss, G.; Zubier, K.; Runte, K.; Turki, A.; Hesse, K.; Jastania, H.; Ladwig, N.; Mudarris, M.
Abstract: This paper presents results of the development and application of a web-based information system, Jeddah CIS, for assisting decision makers in the management of Jeddah coastal waters, in Saudi Arabia. The system will support coastal planning, management of navigation and tackle pollution due to accidents. The system was developed primarily to nowcast in quasi-real time and to deliver short-term forecasts of water levels, current velocities and waves with high spatial and temporal resolution for the area near Jeddah. Therefor it will hasten response when adverse weather conditions prevail. The Jeddah-CIS integrates sensors transmitting in real time, meteorological, oceanographic and water quality parameters and operational models for flow and waves. It also provides interactive tools using advanced visualization techniques to facilitate dissemination of information. The system relies on open source software and has been designed to facilitate the integration of additional components for enhanced information processing, data evaluation and generation of higher water level, current velocity and wave for the general public. Jeddah-CIS has been operational since 2013. Extensions of the system to speed operations and improving the accuracy of the predictions to the public are currently underway. Graphical abstract: Highlights: Coastal Information System for the city of Jeddah, King of Saudi Arabia. Operational system for short term forecast of water levels and waves for the Red Sea. Web based interface to retrieve the information from network of sensors and models. Real time measurements of water levels and waves in the coasts of Jeddah.